2023
DOI: 10.3389/fcvm.2023.1102482
|View full text |Cite
|
Sign up to set email alerts
|

HEARTS in the Americas clinical pathway. Strengthening the decision support system to improve hypertension and cardiovascular disease risk management in primary care settings

Abstract: BackgroundHEARTS in the Americas is the regional adaptation of the WHO Global HEARTS Initiative. It is implemented in 24 countries and over 2,000 primary healthcare facilities. This paper describes the results of a multicomponent, stepwise, quality improvement intervention designed by the HEARTS in the Americas to support advances in hypertension treatment protocols and evolution towards the Clinical Pathway.MethodsThe quality improvement intervention comprised: 1) the use of the appraisal checklist to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…The community-based HEARTS in Americas program is designed to improve hypertension control and the secondary prevention of CVD [ 73 , 74 ]. One of the strategic pillars in the HEARTS in Americas program is the treatment protocol and medication strategy, which aims to improve the availability, quality, and affordability of antihypertensive medications that patients can access, and to use treatment algorithms to simplify decision-making [ 73 ].…”
Section: Regional and National Initiatives To Improve Bp Controlmentioning
confidence: 99%
“…The community-based HEARTS in Americas program is designed to improve hypertension control and the secondary prevention of CVD [ 73 , 74 ]. One of the strategic pillars in the HEARTS in Americas program is the treatment protocol and medication strategy, which aims to improve the availability, quality, and affordability of antihypertensive medications that patients can access, and to use treatment algorithms to simplify decision-making [ 73 ].…”
Section: Regional and National Initiatives To Improve Bp Controlmentioning
confidence: 99%
“…Further, a recent trial by Jiang et al [25] demonstrated the superiority of STPs over usual care in intensive BP reduction as well as reducing cardiovascular disease risk and deaths. The 2023 study by Rosende et al [14], which conducted a similar appraisal of 18 STPs from 16 Latin-American countries (first cohort of 11 countries and a second cohort of 7 additional countries) using the HEARTS checklist, also included a quality improvement intervention that involved expert discussions to solve discrepancies and proposal of a novel clinical pathway to be adopted by the countries. STPs included in this appraisal reported a baseline performance of 65%, which is slightly lower than the observed performance of 68% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It defined the attributes and components of a preferred STPs and developed the ‘HEARTS in the Americas appraisal checklist and its Clinical Pathway’ (HEARTS in the Americas Checklist) [13]. This checklist has been used previously to appraise hypertension treatment STPs from 16 countries in the PAHO region [14]. Outside the PAHO, there has been no review of the availability and quality of the hypertension STPs (hereafter referred to as STPs).…”
Section: Introductionmentioning
confidence: 99%
“…When being explicit about all the necessary conditions for effectiveness, it becomes clear that there are significant challenges to translating HEARTS’ theoretical potential into real-world impact. Some of these challenges, for example, are the lack of long-acting hypertensives and drug combinations in one pill, and non-physician healthcare team members not being able to intensify treatments or difficulties in implementing CVD risk reduction, for example, using high-dose statins, suggest system barriers to achieve the full potential of the strategy 7. Cost might be a significant barrier with estimates of US$9–US$44 per person treated per year, and antihypertensive drugs need to be priced low enough to reach <$5 per patient per year to provide medications alone in the public sector but still can significantly impact national budgets when scaled up 8.…”
Section: What Are the Challenges?mentioning
confidence: 99%